2017
DOI: 10.1149/2.0071703jss
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Silicon Nanowire Roughness and Thermal Conductivity Suppression by Phonon Scattering Mechanisms

Abstract: The nature of the surface roughness of electrolessly etched p-type Si nanowires (NWs) is examined using high resolution transmission electron microscopy and shown to comprise individual silicon nanocrystallites throughout the waviness of the roughness features. As the frequency of roughness features are believed to be sources of surface and boundary scattering, the thermal conductivity below the Casimir limit is still not fully explained. The frequency shift and development of asymmetry in the optical phonon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…The broadening of Raman FWHM is a result of opposite peak shifts of the F 2g mode induced by the tensile and compressive strains in the inner and outer bending regions. 59 It also represents a reduction of phonon mean free path 60 and phonon lifetime. 61,62 Similar to HRTEM and electron diffraction results, the FWHM of the Raman peak reverted to its initial value at the relax state (∼4 cm −1 , about the value for bulk Si 63 ), which further validates the elasticity of the bending process.…”
Section: Origin Of the Remarkable Thermal Conductivitymentioning
confidence: 99%
“…The broadening of Raman FWHM is a result of opposite peak shifts of the F 2g mode induced by the tensile and compressive strains in the inner and outer bending regions. 59 It also represents a reduction of phonon mean free path 60 and phonon lifetime. 61,62 Similar to HRTEM and electron diffraction results, the FWHM of the Raman peak reverted to its initial value at the relax state (∼4 cm −1 , about the value for bulk Si 63 ), which further validates the elasticity of the bending process.…”
Section: Origin Of the Remarkable Thermal Conductivitymentioning
confidence: 99%
“…By using temperature-dependent Raman scattering, we showed that these MACE NWs require 4-phonon processes to explain the Raman scattering shifts. 88,89 The thermal conductivity of the Si NWs was calculated using the same method, with the local temperature calculated using the Raman shift of the zone-center LO phonon. At a laser power of 25 mW under 532 nm excitation, the LO mode shifted to a value of 513.8 cm -1 , corresponding to a local temperature of 600 K. This gives an estimate of the thermal to be in the range 12-18 W mK -1 .…”
Section: Porous Siliconmentioning
confidence: 99%
“…In particular, a conductivity smaller than 10 W/(m K) has been reported in 2003 by Li et al [ 21 ] for monocrystalline silicon nanowires smaller than 30 nm. Since that year, many experimental works have been devoted to the measurement of the thermal conductivity together with other thermoelectric parameters of silicon nanowires and nanostructures [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In 2008, two famous works have been published on Nature Letters: both Hockbaum et al [ 23 ] (who used Metal Assisted Chemical Etching for the production of nanowires) and Boukay et al [ 36 ] reported the thermal conductivity of SiNWs; they positioned one, or very few, nanowires on suspended platforms, completed with microfabricated heaters and thermometers, and both of them achieved a thermal conductivity below 2 W/(m K).…”
Section: Thermoelectric Properties Of Nanostructured Siliconmentioning
confidence: 99%